Pembelajaran Matematika Anak Berkebutuhan Khusus - Maimunah Anabanu (Jurnal Syntax Transformation, 2021)
This research was aimed to analyze the mathematics learning for children with special needs (ABK) in inclusive school X. It was to be able to find out the teacher's and children with special needs problems experienced during the mathematics learning process and the mathematics learning strategies used in the school. The method used in this research is descriptive qualitative method with a case study approach. The information was colleted relatimg with the mathematics learning process of children with special needs. It was obtained by conducting in-depth interviews and observations of the learning process in inclusive schools. The results showed that learning mathematics in inclusive schools X used a scientific approach with the same stages of the learning process as regular schools in general. This was raised various problems, including those experienced by students with special needs including lack of understanding of what is being conveyed, easily forgetting the materials being taught, lazy to do practice questions, difficult to accept learning well, difficult to focus, difficult to memorize formulas, difficult to work on practice independently questions , Often complained and ABK tended to be passive when the learning process. Meanwhile, teacher was difficult to find and adjust the appropriate learning strategies to be implemented in the inclusive class and it was difficult to build the mood of children with special needs. The mathematics learning strategy for children with special needs in inclusive schools X was to maximize the role of the Learning Support Program with the help of a Learning Support Assistant and to work with teachers of mathematics to carry out several efforts such as: Providing special learning; Provide guidance in stages; Build the mood for children with special needs; direct the children with special needs to frequently record mathematical formulas and summarize learning materials; provide flexible media for studying at home and ask ABK to be disciplined students.